History dependent magnetoresistance in lightly doped La2−xSrxCuO4 thin films - Shi, Xiaoyan (2013)
The in-plane magnetoresistance (MR) in atomically smooth La2−xSrxCuO4 thin films grown by molecular-beam-epitaxy was measured in magnetic fields B up to 9 T over a wide range of temperatures T. The films, with x=0.03 and x=0.05, are insulating, and the positive MR emerges at . The positive MR exhibits glassy features, including history dependence and memory, for all orientations of B. The results show that this behavior, which reflects the onset of glassiness in the dynamics of doped holes, is a robust feature of the insulating state.